2013
DOI: 10.1002/wdev.108
|View full text |Cite
|
Sign up to set email alerts
|

Development and plasticity of the Drosophila larval neuromuscular junction

Abstract: The Drosophila larval neuromuscular system is relatively simple, containing only 32 motor neurons in each abdominal hemisegment, and its neuromuscular junctions (NMJs) are large, individually specified, and easy to visualize and record from. NMJ synapses exhibit developmental and functional plasticity while displaying stereotyped connectivity. Drosophila Type I NMJ synapses are glutamatergic, while the vertebrate NMJ uses acetylcholine as its primary neurotransmitter. The larval NMJ synapses use ionotropic glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
215
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(221 citation statements)
references
References 192 publications
(207 reference statements)
3
215
0
Order By: Relevance
“…Mmp1 and Mmp2 both regulate synapse molecular assembly NMJ function is regulated by the number and composition of postsynaptic glutamate receptors (GluRs) juxtaposing presynaptic active zone glutamate release sites (Menon et al, 2013). Since both evoked and spontaneous neurotransmission are altered in Mmp mutants, we next tested how the two Mmp classes might regulate molecular synaptic assembly by quantifying both presynaptic Bruchpilot (Brp) containing active zones (Wagh et al, 2006) and postsynaptic GluR domains (Qin et al, 2005).…”
Section: Mmp1 and Mmp2 Both Regulate Differentiation Of Synapse Functionmentioning
confidence: 99%
“…Mmp1 and Mmp2 both regulate synapse molecular assembly NMJ function is regulated by the number and composition of postsynaptic glutamate receptors (GluRs) juxtaposing presynaptic active zone glutamate release sites (Menon et al, 2013). Since both evoked and spontaneous neurotransmission are altered in Mmp mutants, we next tested how the two Mmp classes might regulate molecular synaptic assembly by quantifying both presynaptic Bruchpilot (Brp) containing active zones (Wagh et al, 2006) and postsynaptic GluR domains (Qin et al, 2005).…”
Section: Mmp1 and Mmp2 Both Regulate Differentiation Of Synapse Functionmentioning
confidence: 99%
“…Therefore, we hypothesized that Mmp regulation is a major determinant of synaptic architecture. The number of synaptic boutons, where neurotransmission occurs, is a robust measure of synaptic architecture, and is furthermore highly plastic over development and in response to activity-dependent modulation (Menon et al, 2013). At the wandering third-instar stage NMJ, each muscle shows a relatively stereotypical pattern of innervation, with similar branching arbors containing a consistent number of synaptic boutons.…”
Section: Timp Constrains the Pattern Of Mmp Proteolytic Activity At Nmentioning
confidence: 99%
“…These synapses are glutamatergic, stereotypically positioned, and resemble mammalian central synapses in terms of the neurotransmitter used [50,51] . Compelling evidence has shown that glia, closely associated with these synapses, modulate synaptic activity and synapse formation [52][53][54][55][56] .…”
Section: Glia-derived Factors During Synapse Formation and Functionmentioning
confidence: 99%